A New Subclass of Analytic Functions Related to Mittag-Leffler Type Poisson Distribution Series - Nazek Alessa; B. Venkateswarlu; P. Thirupathi Reddy; K. Loganathan; K. Tamilvanan (Journal of Function Spaces)
The object of this work is to an innovation of a class k−U~STsℏ,υ,τ,ι,ς in Y with negative coefficients, further determining coefficient estimates, neighborhoods, partial sums, convexity, and compactness of this specified class.